On hidden symmetries of the Skyrme model - Herrera-Aguilar, A.; Kanakoglou, K.; Paschalis, J. E. (HNPS Advances in Nuclear Physics, 2019)
We present a preliminary attempt to establish the existence of hidden nonlinear symmetries of the Skyrme model which could lead to the further integration of the system. An explicit illustration is given for the SU(2) symmetry group.